THE TRANSFORMATION OF THE ONE STOP INTEGRATED SERVICE MANAGEMENT (PTSP) IN IMPROVING THE QUALITY OF PUBLIC SERVICES AT THE MINISTRY OF RELIGIOUS AFFAIRS IN MALANG CITY - Zainal Anwar; Umi Sumbulah; M. Fahim Tharaba; Sutiah Sutiah; Obaidul Hoque (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
This study examines the management transformation of the One-Stop Integrated Service (PTSP) at the Ministry of Religious Affairs in Malang City, which achieved a 92% Public Satisfaction Index (IKM) in 2023 from 78% in 2020, with service time reduced from 4.7 to 1.9 working days. Despite growing literature on PTSP efficiency, no study has comprehensively examined the full management transformation cycle within a religious institution while integrating Islamic values as its normative governance foundation. Using a qualitative case study design, data were collected from key informants comprising structural officials, PTSP staff, service users, and public service experts through in-depth interviews, participatory observation, documentation, and focus group discussions, then analyzed using the Miles, Huberman, and Saldana interactive model. Four novel conceptual constructs emerged: the TRUST model (Transformational Religious-based Unified Service Trust), SMART model (Strategic Management Assessment Responsive Transformation), SERVE model (Service Excellence and Responsive Value Engagement), and ETHIC model (Ethical Transparency and Human-centered Institutional Governance), integrating into the overarching SDG–PTSP model (Spiritual Digital Governance for Public Service Transformation). A key theoretical contribution is the extension of Lewin’s (1947) organizational change model from three to four stages, adding Re-Freeforming as a phase of continuous spiritual-digital renewal unique to religious bureaucracies. Keywords: PTSP transformation; public service quality; digital governance; Islamic values; SDG–PTSP; religious bureaucracy.   Abstrak Studi ini meneliti transformasi manajemen Pelayanan Terpadu Satu Atap (PTSP) di Kementerian Agama Kota Malang, yang mencapai Indeks Kepuasan Masyarakat (IKM) sebesar 92% pada tahun 2023 dari 78% pada tahun 2020, dengan waktu pelayanan berkurang dari 4,7 menjadi 1,9 hari kerja. Meskipun literatur tentang efisiensi PTSP semakin berkembang, belum ada studi yang secara komprehensif meneliti siklus transformasi manajemen secara menyeluruh dalam sebuah lembaga keagamaan sambil mengintegrasikan nilai-nilai Islam sebagai landasan tata kelola normatifnya. Dengan menggunakan desain studi kasus kualitatif, data dikumpulkan dari informan kunci yang terdiri dari pejabat struktural, staf PTSP, pengguna layanan, dan pakar pelayanan publik melalui wawancara mendalam, observasi partisipatif, dokumentasi, dan diskusi kelompok fokus, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Empat konstruksi konseptual baru muncul: model TRUST (Transformational Religious-based Unified Service Trust), model SMART (Strategic Management Assessment Responsive Transformation), model SERVE (Service Excellence and Responsive Value Engagement), dan model ETHIC (Ethical Transparency and Human-centered Institutional Governance), yang terintegrasi ke dalam model SDG–PTSP (Spiritual Digital Governance for Public Service Transformation) yang lebih luas. Kontribusi teoritis utama adalah perluasan model perubahan organisasi Lewin (1947) dari tiga menjadi empat tahap, dengan menambahkan Re-Freeforming sebagai fase pembaruan spiritual-digital berkelanjutan yang unik untuk birokrasi keagamaan. Kata kunci: transformasi PTSP; kualitas publik; digital governance; nilai Islami; birokrasi religius.